Linguistic Landscape: Forms and Functions of Signs on Khaosan Road, Thailand - Rungswang, Atichat (Journal of Roi Kaensarn Academi, 2023)
This study explored linguistic landscape (LL) of Khaosan road, focusing on language use and functions of shop signs. A mixed-method approach was employed by collecting shop signs, categorizing, and conducting in-depth interviews with shop owners. 68 shop signs were collected and 5 shop owners including tattoo, bar, restaurant, souvenir, and jewelry were recruited for the in-depth interviews. The findings revealed that English was immensely used in all aspects. For language use, bilingual signs, English-Thai signs, were found the most followed by English-only signs. Interestingly, Thai-only sign, that is a language of community, was not found at all at Khaosan road. For language functions, using a pair of English and Thai was mostly used to show shop names and English-only information was most frequently used in telling shops’ details and services. Additionally, the qualitative results obtained from in-depth interviews demonstrated the significances of English that can be divided into three themes: a well perceived and understood language, internationalization and national identity and authenticity. Finally, this study discussed how and why English was predominantly used to promote the place.